Clarifying and fostering student autonomy in high-risk educational settings: insights from secondary teachers in Spain and Chile - Rivera-Gómez-Barris, Borja; El Homrani Maknuzi, Mohammed (Frontiers in Education, 2025)
IntroductionEnhancing student autonomy is mandated by the legal frameworks of OECD countries, particularly in vulnerable contexts where it is crucial for individual well-being and life aspirations. Despite its significance, there is limited understanding of teachers’ conceptions and strategies to effectively promote autonomy in the classroom. The present study pursued two complementary aims: first, to propose an interdisciplinary framework, grounded in the Science of Learning and Development (SoLD), to delineate and operationalize student autonomy and establish conditions for its classroom promotion; and second, to analyze teachers’ perceptions of student autonomy, focusing on the importance they assign to it, their theoretical understanding, and the practices they use to foster it in the classroom.MethodsA qualitative approach was employed, using categorical content analysis of eight semi-structured interviews with secondary teachers working with high-risk students. This methodology enabled an in-depth exploration of teachers’ perceptions within settings with similar regulatory requirements.ResultsResults indicate a significant gap between teachers’ valuation of student autonomy and the institutional support they receive: although most recognize its importance, many report lack of support and training, exhibit conceptual uncertainty when defining the concept, and possess limited technical tools to foster it, acknowledging mainly three out of ten key conditions (individual work, adapting to needs, and power sharing). The inclusion of Chile and Spain was conceived as a complementary strategy, rather than a strict comparison, to enrich the understanding of the phenomenon in diverse vulnerable contexts.Discussion/conclusionIn conclusion, while teachers consider autonomy important, they demonstrate greater ability to foster it in practice than to define it theoretically. The study contributes to bridging the gap between theory and practice by operationalizing student autonomy through the SoLD framework, and underscores the urgent need for enhanced teacher education and institutional support to translate curricular mandates into sustainable pedagogical practices.